Mechanistic and Kinetic Investigations of ON/OFF (Photo)Switchable Binding of Carbon Monoxide by Chromium(0), Molybdenum(0) and Tungsten(0) Carbonyl Complexes with a Pyridyl‐Mesoionic Carbene Ligand. Issue 51 (13th July 2022) - Boden, Pit J.; Di Martino‐Fumo, Patrick; Bens, Tobias; Steiger, Sophie T.; Marhöfer, Daniel; Niedner‐Schatteburg, Gereon; Sarkar, Biprajit
Abstract: This work tackles the photochemistry of a series of mononuclear Cr 0, Mo 0 and W 0 carbonyl complexes containing a bidentate mesoionic carbene ligand of the 1, 2, 3‐triazol‐5‐ylidene type. FTIR spectroscopy, combined with density functional theory calculations, revealed a clean photo‐induced reaction in organic solvents (acetonitrile, pyridine, valeronitrile) to give mainly one photoproduct with monosubstitution of a carbonyl ligand for a solvent molecule. The highest photodissociation quantum yields were reached for the Cr 0 complex under UV irradiation (266 nm). Based on previous investigations, the kinetics of the dark reverse reactions have now been determined, with reaction times of up to several hours in pyridine. Photochemical studies in the solid state (KBr matrix, frozen solution) also showed light‐induced reactivity with stabilization of the metastable intermediate with a free coordination site at very low temperature. The identified reactive species emphasizes a mechanism without ligand–sphere reorganization. Abstract : Shining light on group 6 photochemistry : The reversible (photo)chemistry of chromium(0), molybdenum(0) and tungsten(0) carbonyl complexes containing a mesoionic carbene ligand has been investigated. Kinetic and mechanistic studies were performed by using (temperature‐dependent) FTIR and UV/VIS spectroscopy, in combination with density functional theory calculations.